The Mediating Effect on Self-Efficacy in The Relationship Between Gender Identity and Leadership Style - Pohl, Sabine; Desrumaux, Pascale; Vonthron, Anne-Marie (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2020)
According to role congruence theory (Eagly & Karau, 2002), it is not the evaluative content of the stereotype of women but its mismatch with leadership roles that underlies women discrimination with regards to leadership roles. The current study sought to establish whetherleader’s gender identity or the extent to which the leader possesses traits associated with traditional gender stereotypes may explain leadership styles.Using a sample of 163 managers working within bank and personal care services, results show that among both male and female leaders, masculine gender identity was more strongly related to group-focused transformational leadership (charisma, inspirational motivation and idealized influence), transformational intellectual stimulation leadership and to transactional leadership styles. Furthermore, the results show that masculine leadership self-efficacy mediates the relationship between gender identity and leadership styles. Results are discussed in relation to previous research.